Maternal Linguistic Input and Child Language in a Cohort at Risk of Experiencing Social Adversity. Issue 3 (3rd July 2021) - Smith, Jodie; Levickis, Penny; Goldfeld, Sharon; Kemp, Lynn; Conway, Laura
ABSTRACT: Specific features of adult linguistic input may play a larger, or smaller role, at different child ages, across different language outcomes, in different cohorts. This prospective, longitudinal study explored associations between the quantity and quality (i.e. diversity and responsiveness) of maternal linguistic input and child language. This study was derived from an Australian population-based intervention trial. Participants were mother–child dyads at risk of experiencing social adversity ( n = 136). Home visits were conducted at 24 and 36 months. At the 24-month visit, mother–child free-play videos were collected. Seven aspects of maternal linguistic input were measured from videos: imitations, expansions, wh-questions, labels, word types, word tokens and mean length of utterance (MLU). Child language was assessed using a standardized measure at 36 months. Maternal MLU and imitations were associated with overall language and expressive vocabulary scores; wh-questions were associated with receptive language scores. By exploring quantity and quality, we can appreciate the differential contribution of adult linguistic input to early language abilities in different groups of children. Our findings highlight how imitations of early words/sounds and asking children wh-questions may foster expressive and receptive language development. These findings may be helpful to consider when selecting strategies for use in parent-implemented language promotion activities.